ANALISIS YURIDIS ATAS KEBERATAN WARGA PEMILIK TANAH DALAM PELAKSANAAN PENGADAAN TANAH BAGI KEPENTINGAN PEMBANGUNAN DI KOTA LANGSA (STUDI GUGATAN PERDATA NO.8/PDT.G/2012/PN LANGSA) - M U R D A N I M U R D A N I (PREMISE LAW JURNAL, 2015)
The implementation of Law No.2/2012 in the City of Langsa could not run as it should that it resulted in the objection of the traders to public facilites such as the Mushalla (praying room) in the Market, Parking Lot, and Public Toilet or the Open Area which have been truned into the shop building because this is against Law No.2/2012 on land procurement for Development for Public Interest. The result of this study showed that the effectiveness of the implementation of Law No.2/2012 for the development in the City of Langsa was ineffective due to the law morale of the law enforcers (the goverment). The contraints faced by City Goverment of Langsa in the implementation of the Law were the developer as the agent of Goverment that had tried to smuggle the law. The insuance of Master Plan without being socialized before the public and the lack of legal awareness within the Goverment/Developer. The solution to determine or make a work agreement with individual or legal entity as the implementer of the development in the City of Langsa should have inclouded the clear sanctions in the work agreement so that the implementer is afraid to arbitrarily treat the community members. The element of the former Old Terminal trader community shoud  have been involved as the implementer of development. Keywords : Juridical Analysis, Land Acquisition, Interest of Development